Into the EU : Policy Frameworks in Central Europe. (International Monetary Fund, 2002)
This book examines the opportunities and challenges involved for five central European applicants-the Czech Republic, Hungary, Poland, the Slovak Republic, and Slovenia-in joining the European Union. The central focus is on the issues that policymakers in central Europe face as they craft macroeconomic and financial sector policies to help ensure growth that is both strong and sustainable, in a setting that may feature large and potentially volatile capital flows. It examines the competing pressures on these countries in the run-up to EU accession later, and monetary union.